Manufacturing method of rare earth sintered magnet
By adjusting the moisture ratio during the cutting process of rare earth sintered magnets, the method addresses the challenge of controlling grain boundary thickness and oxygen concentration, resulting in improved magnet properties.
Patent Information
- Application Number
- JP2023164461
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing methods for manufacturing rare earth sintered magnets struggle to control the thickness of two-particle grain boundaries, leading to irregular magnet properties due to variations in oxygen concentration, especially during the cutting process of wet powder molded bodies.
The method involves cutting a wet powder molded body in an oil agent while adjusting the moisture ratio, defined as the ratio of water mass in the oil to the mass of recycled raw material powder, to 0.15% or less, thereby suppressing oxidation and allowing for precise control of grain boundary phases.
This approach effectively suppresses the oxidation of recycled raw material powder, enabling the production of rare earth sintered magnets with modified two-particle grain boundaries and improved magnetic properties.
Smart Images

Figure 2025055179000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a rare earth sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is a rare earth element that must contain at least one of Nd and Pr. T is Fe and Co, with over 90% of T being Fe by mass. B is boron) are a representative example of rare earth sintered magnets, and are known as the most high-performance permanent magnets, and are used in a variety of motors, including those for electric vehicles (EV, HV, PHV, etc.), industrial equipment, and home appliances. RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located at the grain boundary portion of this main phase. 14 The B compound is a ferromagnetic phase with high magnetization.
[0003] RTB sintered magnets have a coercive force H cJ (Hereinafter, simply "coercive force" or "H cJ This causes a problem of irreversible thermal demagnetization, as the magnetization temperature drops and the magnetization rate drops. For this reason, RTB sintered magnets, which are used in electric vehicle motors in particular, have a high H cJ It is required that the applicant have:
[0004] In RTB sintered magnets, R2T 14 When a part of the light rare earth elements (mainly Nd and / or Pr) contained in R in the B compound is replaced with heavy rare earth elements (mainly Dy and / or Tb), H cJ It is known that the H cJ will improve.
[0005] However, R2T 14 When the light rare earth elements in the B compound are replaced with heavy rare earth elements, the H of the RTB sintered magnet cJ While the residual magnetic flux density B r(Hereinafter, simply "B r In addition, heavy rare earth elements, especially Dy, are scarce and have limited production areas, so their supply is unstable and their prices fluctuate greatly. For this reason, in recent years, users have been promoting the use of H as little as possible without using heavy rare earth elements. cJ There is a need to improve this.
[0006] Patent Document 1 discloses an RTB rare earth sintered magnet with increased coercivity while reducing the Dy content. The composition of this sintered magnet is limited to a specific range in which the amount of B (boron composition ratio or boron concentration) is relatively low compared to commonly used RTB alloys, and contains one or more metal elements selected from Al, Ga, and Cu. As a result, R2T occurs at the grain boundaries. 17 Phase is generated and this R2T 17 Transition metal-rich phase (R6T 13 As the volume ratio of H cJ will improve. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 008756 Summary of the Invention [Problem to be solved by the invention]
[0008] High B while reducing the content of heavy rare earth elements r and high H cJ In order to realize a rare earth sintered magnet with this property, a technology is being investigated in which the thickness of the two-particle grain boundary is controlled by relatively reducing the amount of B.
[0009] On the other hand, it was found that even if the amount of rare earth elements and the amount of B in the raw alloy are adjusted to the desired range, the thickness of the two-particle grain boundary may not be sufficiently controlled depending on the manufacturing process, resulting in deterioration of the magnetic properties. This is thought to be because the grain boundary phase changes depending on the amount of oxygen in the rare earth sintered magnet. However, it was found that it is difficult to control the variation in the oxygen concentration of the finally obtained rare earth sintered magnet to 0.12 mass% or less even if each process in the manufacturing stage is controlled in a low-oxygen atmosphere. In particular, it was found that in the process of cutting the wet powder compact in the oil solution described below, the powder of the recycled raw material generated by the cutting may be oxidized by the moisture in the oil solution. As a result, when a rare earth sintered magnet containing the powder of the recycled raw material was manufactured, it was sometimes impossible to obtain a rare earth sintered magnet with a modified two-particle grain boundary. [Means for solving the problem]
[0010] In one embodiment, a method for producing a rare earth sintered magnet according to the present disclosure includes the steps of placing a wet powder compact of a rare earth raw alloy in a cutting device and cutting the wet powder compact in an oil agent, and adjusting a moisture ratio in the oil agent, which is the ratio of the mass of moisture in the oil agent to the mass of recycled raw material powder generated by the step of cutting the wet powder compact, to 0.15% or less. Effect of the Invention
[0011] According to an embodiment of the present disclosure, the moisture ratio, which is the ratio of the mass of moisture in the oil to the mass of the powder of the recycled raw material generated by the process of cutting the wet powder compact in the oil, can be adjusted to 0.15% or less, thereby preventing the powder of the recycled raw material from being oxidized by the moisture in the oil. As a result, when a rare earth sintered magnet is produced that contains the powder of the recycled raw material, it is possible to realize a rare earth sintered magnet with a modified two-particle grain boundary. [Brief description of the drawings]
[0012] [Figure 1A]FIG. 2 is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet. [Figure 1B] FIG. 1B is a further enlarged schematic diagram of the dashed rectangular area in FIG. 1A. [Diagram 2] 1 is a flowchart outlining a method for producing a rare earth sintered magnet according to an embodiment of the present disclosure. [Figure 3A] FIG. 11 is a front view for explaining a step of cutting a wet powder compact submerged in an oil agent with a wire. [Figure 3B] FIG. 11 is another front view illustrating the step of cutting the wet powder compact submerged in the oil with a wire. [Figure 4] 5 is another flowchart showing an outline of the method for producing a rare earth sintered magnet according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present disclosure will be described using an RTB sintered magnet as an example of a rare earth sintered magnet.
[0014] Conventionally, in an RTB sintered magnet, for example, when (1) the content of R (at least one of rare earth elements, which necessarily contains at least one of Nd and Pr) is 27 mass% or more and 34 mass% or less of the entire RTB sintered magnet, (2) T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, T necessarily contains Fe, and the content of Fe in the entire T is 80 mass% or more, and (3) the molar ratio of T to B ([T] / [B]) is more than 14.0 and 15.0 or less, an element such as Ga is added to thicken the two-particle grain boundary and increase the H cJ It is known that it is possible to improve
[0015] The molar ratio of T to B ([T] / [B]) is the ratio (a / b) of the number of moles (a) obtained by dividing the analytical value (mass%) of the concentration of each element (Fe and at least one of Co, Al, Mn, and Si) constituting T by the atomic weight of each element, to the number of moles (b) obtained by dividing the analytical value (mass%) of the concentration of B by the atomic weight of B.
[0016] When the molar ratio of T to B ([T] / [B]) exceeds 14.0, the B content is R2T 14 This means that the stoichiometric composition ratio of the B compound is lower than that of the main phase (R2T 14 The amount of B is reduced relative to the amount of T used to form the cation exchange reaction (compound B).
[0017] Next, the basic structure of an RTB based sintered magnet will be described.
[0018] RTB sintered magnets have a structure in which powder particles of raw alloys are bonded together by sintering, and are mainly 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundaries of the main phase.
[0019] FIG. 1A is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet, and FIG. 1B is a schematic diagram further enlarging the dashed rectangular area in FIG. 1A. In FIG. 1A, an arrow of 5 μm in length is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB based sintered magnet is mainly composed of R2T 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R2T 14 B compound grains are adjacent to each other in the two-particle grain boundary phase 14a, and there are three or more R2T 14 The B compound grains include adjacent grain boundary triple junctions 14b.
[0020] R2T, which is main phase 12 14The B compound is a ferromagnetic phase with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the R2T 14 By increasing the proportion of B compounds, r It can improve R2T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R2T 14 The best way is to get the stoichiometric ratio of B compound (R amount:T amount:B amount = 2:14:1). 14 When the amount of B or R for forming the B compound is less than the stoichiometric ratio, the grain boundary phase 14 generally contains an Fe phase or an R2T phase. 17 Soft magnetic phases such as H cJ However, the amount of B is reduced by R2T 14 When the amount of B compound is less than the stoichiometric ratio and one or more metal elements M selected from Al, Ga, and Cu are contained, R2T 17 The grain boundaries become thicker due to the formation of transition metal-rich phases (e.g., RT-Ga phases) at the grain boundaries from the phase, resulting in high H cJ can be obtained.
[0021] In RTB sintered magnets, in order to thicken the two-particle boundary, it is important to control not only the amount of B but also the amount of oxygen. According to the study by the present inventors, in order to precisely control the amount of oxygen contained in the RTB sintered magnet material within a predetermined range, it is important to prevent the wet powder compact from coming into contact with the air and to suppress oxidation caused by the moisture in the oil by immersing the wet powder compact in an oil having an adjusted moisture content when cutting the wet powder compact. In addition, in the embodiment of the present disclosure, it is found that it is possible to more effectively suppress the oxidation of the powder by managing and controlling the moisture content of the oil in accordance with the mass of the powder of the recycled raw material generated by the process of cutting the wet powder compact, rather than simply reducing the moisture content of the oil. The powder of the recycled raw material refers to the powder (swarf) of the wet powder compact generated by cutting the wet powder compact.
[0022] <Embodiment> Next, an outline of the method for producing a rare earth sintered magnet of this embodiment will be described with reference to Fig. 2. As shown in Fig. 2, the method for producing a rare earth sintered magnet of this embodiment includes the steps of placing a wet powder compact of a rare earth-based raw alloy in a cutting device and cutting the wet powder compact in an oil agent, and adjusting the moisture ratio, which is the ratio of the moisture mass in the oil agent to the mass of the powder of the recycled raw material generated by the step of cutting the wet powder compact, to 0.15% or less.
[0023] The important point of the manufacturing method in this embodiment is to adjust the "moisture ratio" in the oil stored in the cutting device to 0.15% or less. The technical effect of this will be described later.
[0024] Hereinafter, each step in the manufacturing method of this embodiment, including the above steps, will be described.
[0025] <Step of forming rare earth alloy powder> In this embodiment, a step of forming rare earth alloy powder using a jet mill pulverizer is performed as a step of pulverizing the raw alloy to obtain rare earth alloy powder (fine pulverization step). Prior to the fine pulverization step, a hydrogen pulverization step is preferably performed to prepare coarsely pulverized rare earth alloy powder. Here, the composition of the rare earth alloy raw material is as follows: R: 26.5 to 33.5 mass% (R is a rare earth element and must contain at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85~0.92% by mass, T: 61.5 mass% or more (T is Fe and Co, and 90% or more of T is Fe by mass ratio), Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less
[0026] By adjusting the amount of B to the above range, R6T is formed at the grain boundaries of rare earth sintered magnets. 13Ga is formed and the two-grain boundary becomes thicker, for example, B of 1.39T or more. r and high H exceeding 1640kA / m cJ In order to reliably thicken the two-particle grain boundary, it is more preferable that the molar ratio of T ([T] / [B]) is more than 14.0 and 15.0 or less.
[0027] The rare earth-based raw alloy having the above composition can be produced, for example, by a strip casting method. The rare earth-based alloy may contain a plurality of alloy components having different compositions. By having the above composition as a whole, the above-mentioned two-particle grain boundary is thickened to obtain a high H cJ It is possible to obtain the effect of realizing the above.
[0028] The hydrogen pulverization process may include a hydrogen absorption process in which hydrogen is absorbed into the rare earth alloy at a temperature of 200°C or less in a treatment chamber, and a dehydrogenation process in which hydrogen is exhausted from inside the treatment chamber and the rare earth alloy is heated to a temperature in the range of, for example, 80°C or more and 650°C or less to perform a dehydrogenation process and produce a coarsely pulverized powder.
[0029] The average particle size of the coarsely pulverized powder is, for example, 10 μm or more and 500 μm or less. The average particle size (d50) in this disclosure can be measured by an airflow dispersion type laser diffraction method (based on JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter: d50) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.
[0030] In the fine pulverization step (S10), the coarsely pulverized powder is pulverized to obtain a fine powder having a median diameter d50 of, for example, 3.5 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely pulverized powder. An example of the organic grinding aid is zinc stearate. The average particle size d50 of the finely pulverized powder is preferably 2.0 μm or more and 3.5 μm or less.
[0031] The method for producing a rare earth sintered magnet includes the steps of producing a wet powder compact using the finely pulverized powder produced by the above method, and producing a rare earth sintered magnet material by sintering the wet powder compact. The press molding method (press molding in a magnetic field) used to produce the wet powder compact is, for example, a wet molding method. In the wet molding method, a slurry in which the powder is dispersed in oil is used, and the powder is supplied in the form of a slurry into a die and press molded.
[0032] When wet molding is used, the wet powder compact may come into contact with something during transportation, causing chipping or cracking, resulting in defective products. In some cases, a single wet powder compact may be cut into multiple compact pieces. The compact pieces are transformed into rare earth sintered magnet material through a sintering process, but the parts of the wet powder compact other than the compact pieces are not sintered and remain as "waste."
[0033] Since the rare earth metals used in rare earth sintered magnets are scarce elements, it is desirable to effectively reuse such scraps.
[0034] An example of a process for producing a wet powder compact from the above powder will now be described.
[0035] <Process for Producing Wet Powder Compact> The wet powder compact can be produced from the powder (finely pulverized powder) by, for example, pressing in a magnetic field. From the viewpoint of suppressing oxidation in pressing in a magnetic field, it is preferable to form the wet powder compact by wet pressing. In particular, in wet pressing, the surfaces of the particles constituting the wet powder compact are covered with an oil agent, suppressing contact with oxygen and water vapor in the air. Therefore, it is possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing process.
[0036] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing the finely pulverized powder with an oil agent, and the slurry is supplied to a cavity in a die of a wet pressing apparatus and press-molded in a magnetic field. The oil agent is a liquid that can obtain a slurry by dispersing the alloy powder inside the oil agent. A preferred oil agent used in the present disclosure can be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increase in viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet pressing in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. In addition, if the fractional point of the mineral oil or synthetic oil exceeds 400°C, it becomes difficult to remove the oil after obtaining a molded body, and the amount of residual carbon in the sintered body may increase, resulting in a deterioration of the magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. In addition, vegetable oil may be used as the oil agent. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.
[0037] The obtained alloy powder and an oil agent are mixed to obtain a slurry. The mixing ratio of the alloy powder and the oil agent is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3This is because at a flow rate of 1000 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the oil agent is not particularly limited. The alloy powder and the oil agent may be prepared separately, and then the alloy powder and the oil agent may be weighed and mixed in a predetermined amount. In addition, when the coarsely pulverized powder is dry-pulverized with a jet mill or the like to obtain the alloy powder, a recovery container containing the oil agent may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly recovered in the oil agent in the recovery container to obtain the slurry. In this case, it is preferable that the atmosphere inside the recovery container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly recovered in the oil agent without being exposed to the air to obtain the slurry. Furthermore, it is also possible to wet-pulverize the coarsely pulverized powder in the oil agent using a vibration mill, ball mill, attritor, or the like to obtain a slurry consisting of the alloy powder and the oil agent.
[0038] The slurry thus obtained is molded in a known wet press to obtain a molded body having a desired size and shape. Specifically, the slurry is supplied to a cavity in a mold of the wet press molding device and press molded in a magnetic field. The wet powder molded body is, for example, 4 g / cm 3 More than 5g / cm 3 It may have the following densities:
[0039] <Step of cutting the wet powder compact (S10)> In this embodiment, the wet powder compacts obtained by the above steps are cut by, for example, a wire saw device (cutting device) to produce one or more compact pieces from each wet powder compact. More specifically, the wet powder compacts of the rare earth-based raw alloy are placed in the oil of the wire saw device that stores the oil, and the wet powder compacts are cut in the oil.
[0040] In the following description, the cutting of the wet powder compact 10 can be performed, for example, by a wire saw device 100 shown in FIG. 3A and FIG. 3B. FIG. 3A and FIG. 3B are explanatory diagrams for explaining the process of cutting the wet powder compact 10 submerged in the oil agent 60 with the wire 40, respectively. FIG. 3A shows a state before the cutting process starts, and FIG. 3B shows a state during the cutting process. The dashed line in the wet powder compact 10 shown in FIG. 3B shows a schematic position of the wire 40 while cutting the wet powder compact 10. For reference, the figure shows the X-axis, Y-axis, and Z-axis that are mutually orthogonal. In this example, the XY plane is horizontal, and the Z-axis is vertical.
[0041] In this embodiment, the wire saw device 100 has rollers 30a, 30b, and 30c arranged so that the central axes of rotation are parallel to each other, and a single continuous wire 40. Each of the rollers 30a to 30c is rotatably supported by a support device (not shown). The rotation axes of the rollers 30a to 30c are parallel to the Y-axis. The wire 40 runs under tension due to the rotation of the rollers 30a to 30c. The wire 40 is wound up on a bobbin (not shown) or the like. The wire saw device 100 may further include other rollers for adjusting the tension, etc.
[0042] The wet powder compact 10 is fixed to a fixing base 20 and placed inside a tank 62 that stores an oil agent 60. The entire wet powder compact 10 is immersed in the oil agent 60. Of the traveling wire 40, a portion located between rollers 30a and 30b comes into contact with the wet powder compact 10. A supporting device (not shown) has a shape that allows it to move in the Y-axis direction without interfering with the wet powder compact 10 when the wet powder compact 10 is being cut by the wire 40 traveling between rollers 30a and 30b.
[0043] In the illustrated example, the wire 40 travels in the X-axis direction at a predetermined speed while moving in a direction perpendicular to the traveling direction of the wire 40 (X-axis direction) (any direction in the YZ plane). The direction perpendicular to the traveling direction of the wire 40 is the cutting direction, and the speed in this direction (cutting speed) is set to, for example, 100 mm / min or more. In the example shown in FIG. 3B, the traveling wire 40 moves, for example, in the negative direction of the Z-axis relative to the stationary wet powder compact 10, but as described above, the wet powder compact 10 may be lifted together with the fixing base 20 in the positive direction of the Z-axis, or may have a movement component in the Y-axis direction.
[0044] In this embodiment, the wet powder molding 10 is immersed in the oil 60 stored in the tank 62 of the cutting device, so that the powder constituting the wet powder molding 10 is prevented from coming into contact with the atmospheric gas, and direct oxidation by water vapor in the air can be suppressed.
[0045] However, according to the study by the present inventors, it was found that if the wet powder molding is immersed in the oil agent 60 for a long time, the powder is oxidized by the moisture in the oil agent 60, and the oxygen concentration of the powder increases. For this reason, in the embodiment of the present disclosure, the moisture content of the oil agent 60 is controlled to suppress the oxidation of the powder.
[0046] <Step (S12) of adjusting the moisture ratio to 0.15% or less> In this embodiment, the moisture content in the oil agent 60 is not simply reduced, but the moisture ratio, which is the ratio of the "moisture mass in the oil agent" to the "mass of powder in the oil agent 60 (powder generated by cutting (powder of recycled raw material))", is adjusted to 0.15% or less. The mass of the powder (powder of recycled raw material) in the oil agent 60 can be obtained from the cutting distance, cutting width, etc. of the wet compact to be cut. Also, the mass of the recycled raw material may be confirmed in advance through an experiment. The moisture content of the oil agent 60 can be adjusted by passing an inert gas through the oil agent 60 to reduce the moisture mass in the oil agent 60. Preferably, the moisture ratio is 0.10% or less. The moisture ratio can be measured using a known moisture-in-oil meter, for example, a moisture-in-oil meter TEKHNEPort-Oil manufactured by TEKHNE Measurement Co., Ltd.
[0047] Through experiments by the inventors, it has been found that by adjusting this moisture ratio to 0.15% or less, the oxygen increase in a rare earth sintered magnet produced through a cutting process in oil for, for example, 5 minutes or more can be suppressed to 0.12 mass% or less.
[0048] According to the wire saw device 100, one or more pieces of compacts having various shapes, possibly including curved surfaces, can be produced from a block-shaped wet powder compact 10 having, for example, a rectangular parallelepiped shape. At this time, unsintered waste material is also produced from each wet powder compact 10.
[0049] Next, refer to Fig. 4. The method for producing a rare earth sintered magnet in this embodiment includes a step (S16) of recovering the recycled raw material powder generated by the above cutting step, a step (S18) of producing a wet powder compact containing the recycled raw material powder, and a step (S20) of sintering the wet powder compact to produce a rare earth sintered magnet material. More preferably, the method further includes a step (S22) of preparing a diffusion source powder made of an RMA alloy, and a step (S24) of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material to diffuse elements contained in the diffusion source powder into the rare earth sintered magnet material.
[0050] Examples of each of the above steps will now be described.
[0051] <Step of recovering powder of recycled raw materials generated by the cutting step (S16)> In this embodiment, the powder (powder of the recycled raw material) generated by cutting such a wet powder compact 10 is collected for reuse. In addition, the powder obtained by crushing the cut waste material by a crushing device may be mixed with the powder of the recycled raw material. In addition, both the powder of the recycled raw material and the scraps may be put into a crushing device and crushed. As a crushing method, for example, crushing can be performed so as to include powder that is 149 mesh pass 500 mesh on. The waste material may be crushed by simply crushing it with a stainless steel member or the like, or may be crushed using a device such as those described in International Publication No. 2011 / 125578 or International Publication No. 2013 / 047429. In the powder after crushing, the higher the ratio of the powder that is 149 mesh pass, the more preferable it is, for example, 10 mass% or more, 25 mass% or more, 50 mass% or more, 75 mass% or more, 90 mass% or more, and 100 mass% are preferable in this order. This can further improve the yield of the regenerated powder. In addition, the higher the ratio of the 500 mesh on powder in the powder after crushing, the more preferable it is, for example, 10 mass% or more, 25 mass% or more, 50 mass% or more, 75 mass% or more, 90 mass% or more, and 100 mass% are preferable in this order. This makes it possible to further shorten the time required for crushing compared to the conventional technology in which all the powders in the crushing process were 500 mesh pass. More preferably, the powder after crushing is made up of 149 mesh pass, 500 mesh on powder. The state of the powder after crushing is not limited to the above example.
[0052] The reusable powder thus obtained can be preferably reused by mixing with a powder produced, for example, by a jet mill grinding device. The slurry obtained by mixing can be used to produce a new wet powder compact by the above-mentioned wet pressing.
[0053] <Step (S18) of producing a wet powder compact containing recycled raw material powder> The wet powder compact containing the recycled raw material powder can be produced, for example, by the method described above in <Step of producing wet powder compact>, and therefore detailed description will not be repeated here.
[0054] <Step of Producing Sintered Rare Earth Magnet Material (S20)> Next, the wet powder compact is sintered to obtain a rare earth sintered magnet body (sintered body).
[0055] The sintering of the wet powder compact is preferably carried out at a temperature in the range of 1000°C to 1150°C. To prevent oxidation due to sintering, residual gas in the atmosphere may be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably subjected to a heat treatment. The magnetic properties can be improved by the heat treatment. Known conditions for the heat treatment, such as the heat treatment temperature and heat treatment time, can be adopted. The rare earth sintered magnet body thus obtained is subjected to a grinding / polishing process, a surface treatment process, and a magnetization process as necessary to complete the final rare earth sintered magnet.
[0056] <Step of Preparing Diffusion Source Powder (S22)> In the RMA alloy, which is a diffusion source, R is at least one rare earth element, including at least one of Nd and Pr. M is at least one selected from the group consisting of Cu, Ga, Co, and Fe. A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B.
[0057] The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire RMA alloy, the composition ratio of M is 5% by mass or more and 35% by mass or less of the entire RMA alloy, and the composition ratio of A is 0% by mass or more and 3% by mass or less of the entire RMA alloy.
[0058] The diffusion source can be prepared by a method for preparing a raw material alloy that is employed in a general manufacturing method typified by Nd-Fe-B sintered magnets, such as a die casting method, a strip casting method, a single roll super-quenching method (melt spinning method), or an atomizing method. The diffusion source may also be an alloy obtained by the above method, which has been pulverized by a known pulverizing means such as a pin mill. In order to improve the pulverizability of the alloy obtained by the above method, the alloy may be subjected to a heat treatment at 700°C or less in a hydrogen atmosphere to incorporate hydrogen, and then pulverized.
[0059] <Diffusion step of elements contained in diffusion source powder (S24)> By performing heat treatment at a temperature of 700°C or higher and 1100°C or lower in a vacuum or inert gas atmosphere, the elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. In the present disclosure, this heat treatment is referred to as the first heat treatment. If the heat treatment temperature for diffusion is less than 700°C, the diffusion is insufficient and a high H cJ On the other hand, if the temperature exceeds 1100℃, abnormal grain growth of the main phase occurs, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. cJ The heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material and the diffusion source, the heat treatment temperature, etc., but is preferably 5 minutes to 30 hours, more preferably 10 minutes to 25 hours, and even more preferably 30 minutes to 20 hours. It is also preferable to prepare the diffusion source in an amount of 1 mass% to 30 mass% of the weight of the sintered body material. If the diffusion source is less than 1 mass% of the weight of the sintered body material, H cJ On the other hand, if it exceeds 30 mass%, B r may decrease.
[0060] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the surface of the sintered body material can be covered with a powder layer of the diffusion source, and the first heat treatment can be performed. For example, the diffusion source can be coated on the surface of the sintered body material by a sputtering method, and then the first heat treatment can be performed. For example, a slurry in which the diffusion source is dispersed in an oil agent can be applied to the surface of the sintered body material, and the oil agent can be evaporated to bring the diffusion source into contact with the sintered body material. Examples of the oil agent include alcohol (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes, and ketones. In addition, the sintered body material that has been subjected to the first heat treatment can be subjected to known mechanical processing such as cutting or machining.
[0061] The sintered body material that has been subjected to the heat treatment for diffusion may be subjected to a heat treatment at a temperature of 450° C. or more and 600° C. or less in a vacuum or in an inert gas atmosphere. In the present disclosure, this heat treatment is referred to as a second heat treatment. By performing the second heat treatment, a high B r and high H cJ By setting the temperature of the second heat treatment to 450° C. or more and 600° C. or less, R6T 13 The formation of the Ga phase progresses. The second heat treatment temperature is preferably 480°C or higher and 560°C or lower. cJ The heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material, the heat treatment temperature, etc., and is preferably from 5 minutes to 20 hours, more preferably from 10 minutes to 15 hours, and even more preferably from 30 minutes to 10 hours. EXAMPLES
[0062] The present disclosure will be described in more detail below with reference to experimental examples (including examples and comparative examples); however, the present disclosure is not limited thereto.
[0063] Experimental Example 1 A rare earth-based raw alloy (alloy for RTB-based sintered magnets) shown in Sample No. 1 in Table 1 was prepared. Specifically, an alloy of each element was prepared so as to have the composition shown in Sample No. 1 in Table 1, and an alloy for RTB-based sintered magnets was produced by strip casting. The obtained alloy for RTB-based sintered magnets was coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powder. The coarsely pulverized powder was fed into a jet mill pulverizer and pulverized to obtain fine powder. The average particle size (d50) of the obtained fine powder was 3.0 μm. The average particle size (d50) was measured using a particle size distribution analyzer "HELOS&RODOS" manufactured by Sympatec under the following conditions: dispersion pressure: 4 bar, measurement range: R2, calculation mode: HRLD.
[0064] The obtained fine powder was immersed in mineral oil to prepare a slurry. The slurry concentration was 75% by mass. The obtained slurry was molded (wet molding) in a magnetic field to obtain a wet powder compact. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other. The wet powder compact was placed in a cutting device (wire saw device) shown in Figures 3A and B, and cut in the oil. The moisture ratio, which is the ratio of the moisture mass in the oil to the mass of the powder of the recycled raw material generated by cutting the wet powder compact in the oil, was adjusted as shown in Table 2. The moisture ratio was measured using a moisture meter in oil, TEKHNE Port-Oil, manufactured by Techne Measurement Co., Ltd.
[0065] The powder of the recycled raw materials generated by cutting was collected, and a wet powder compact was produced from the powder of the recycled raw materials in the same manner. The wet powder compact obtained was sintered in a vacuum at 1050°C (a temperature selected so that sufficient densification by sintering occurs) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m 3 The sintered bodies were then subjected to a heat treatment in which they were held at 800°C for 2 hours, cooled to room temperature, and then held at 500°C for 2 hours, and cooled to room temperature, to obtain RTB sintered magnets (Nos. 1 to 6).
[0066] The O (oxygen content) of the obtained sintered magnet was measured using a gas fusion-infrared absorption method. The results are shown in Table 2. In addition, an RTB based sintered magnet (No. A) was produced from a wet powder compact in the same manner (an RTB based sintered magnet produced from a wet powder compact that had not been cut). The oxygen content of the produced magnet was measured and found to be 0.093 mass%. The difference in oxygen content (△oxygen) between the RTB based sintered magnet No. A and the RTB based sintered magnets Nos. 1 to 6 is shown in Table 2.
[0067] [Table 1]
[0068] [Table 2]
[0069] As shown in Table 2, the present examples (Nos. 5 and 6) have a lower oxygen content than the comparative examples (Nos. 1 to 4), and the Δoxygen content is controlled to 1200 ppm or less.
[0070] As described above, the present disclosure includes the methods for producing sintered rare earth magnets described in the following items.
[0071] [Item 1] placing a wet powder compact of a rare earth-based raw alloy in a cutting device and cutting the wet powder compact in an oil; adjusting a moisture ratio, which is a ratio of the moisture mass in the oil to the mass of the powder of the recycled raw material generated by the cutting of the wet powder compact, to 0.15% or less; The method for producing a rare earth sintered magnet includes the steps of: [Item 2] 2. The method for producing a rare earth sintered magnet according to item 1, wherein the step of adjusting the moisture ratio to 0.15% or less comprises a step of passing an inert gas through the oil agent to reduce the moisture mass in the oil agent. [Item 3] The composition of the rare earth-based raw alloy is R: 26.5 to 33.5 mass% (R is a rare earth element and must contain at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85~0.92% by mass, T: 61.5 mass% or more (T is Fe and Co, and 90% or more of T is Fe by mass ratio), Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less 3. The method for producing a rare earth sintered magnet according to item 1 or 2, [Item 4] a step of recovering a powder of a recycling material generated by a step of cutting the wet powder compact; preparing a wet powder compact containing the recycled raw material powder; a step of sintering a wet powder compact containing the recycled raw material powder to produce a rare earth sintered magnet material; providing a diffusion source powder formed from an RMA alloy; a step of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material; Further comprising: In the RMA alloy, R is at least one rare earth element, including at least one of Nd and Pr; M is at least one selected from the group consisting of Cu, Ga, Co, and Fe; A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B; The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire RMA alloy. The composition ratio of M is 5% by mass or more and 35% by mass or less of the entire RMA alloy. 4. The method for producing a rare earth sintered magnet according to any one of items 1 to 3, wherein the composition ratio of A is from 0 to 3 mass % of the entire RMA alloy. [Item 5] a step of recovering a powder of a recycling material generated by a step of cutting the wet powder compact; preparing a rare earth-based raw material alloy containing the recycled raw material; producing a wet powder compact using the rare earth-based raw alloy; a step of sintering the wet powder compact to produce a rare earth sintered magnet material; providing a diffusion source powder formed from an RMA alloy; a step of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material; Further comprising: In the RMA alloy, R is at least one rare earth element, including at least one of Nd and Pr; M is at least one selected from the group consisting of Cu, Ga, Co, and Fe; A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B; The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire RMA alloy. The composition ratio of M is 5% by mass or more and 35% by mass or less of the entire RMA alloy. 4. The method for producing a rare earth sintered magnet according to any one of items 1 to 3, wherein the composition ratio of A is from 0 to 3 mass % of the entire RMA alloy. [Explanation of symbols]
[0072] 12 Main phase 14 Grain boundary phase 14a Two-grain grain boundary phase 14b Grain boundary triple point
Claims
1. placing a wet powder compact of a rare earth-based raw alloy in a cutting device and cutting the wet powder compact in an oil; adjusting a moisture ratio, which is a ratio of the moisture mass in the oil to the mass of the powder of the recycled raw material generated by the cutting of the wet powder compact, to 0.15% or less; The method for producing a rare earth sintered magnet includes the steps of:
2. 2. The method for producing a rare earth sintered magnet according to claim 1, wherein the step of adjusting the moisture ratio to 0.15% or less includes a step of passing an inert gas through the oil to reduce the moisture mass in the oil.
3. The composition of the rare earth-based raw alloy is R: 26.5 to 33.5 mass% (R is a rare earth element and must contain at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85 to 0.92% by mass, T: 61.5 mass% or more (T is Fe and Co, and 90% or more of T is Fe by mass ratio); Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less The method for producing a rare earth sintered magnet according to claim 1,
4. a step of recovering a powder of a recycling material generated by a step of cutting the wet powder compact; preparing a wet powder compact containing the recycled raw material powder; a step of sintering a wet powder compact containing the recycled raw material powder to produce a rare earth sintered magnet material; providing a diffusion source powder formed from an R-M-A alloy; a step of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material; Further comprising: In the R-M-A alloy, R is at least one rare earth element, including at least one of Nd and Pr; M is at least one selected from the group consisting of Cu, Ga, Co, and Fe; A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B; The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire R-M-A alloy, The composition ratio of M is 5% by mass or more and 35% by mass or less of the entire R-M-A alloy, 4. The method for producing a rare earth sintered magnet according to claim 3, wherein the composition ratio of A is from 0% to 3% by mass of the entire RMA alloy.
5. a step of recovering a powder of a recycling material generated by a step of cutting the wet powder compact; preparing a rare earth-based raw material alloy containing the recycled raw material powder; producing a wet powder compact using the rare earth-based raw alloy; a step of sintering the wet powder compact to produce a rare earth sintered magnet material; providing a diffusion source powder formed from an R-M-A alloy; a step of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material; Further comprising: In the R-M-A alloy, R is at least one rare earth element, including at least one of Nd and Pr; M is at least one selected from the group consisting of Cu, Ga, Co, and Fe; A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B; The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire R-M-A alloy, The composition ratio of M is 5% by mass or more and 35% by mass or less of the entire R-M-A alloy, 4. The method for producing a rare earth sintered magnet according to claim 3, wherein the composition ratio of A is from 0% to 3% by mass of the entire RMA alloy.
Citation Information
Patent Citations
Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor
WO2013008756A1